Assessment of fruit and vegetable consumption among female university students - Ahmad Sirfan, Ainin Sofiya; Hamirudin, Aliza Haslinda; Sidek, Suriati (Rynnye Lyan Resources, 2020)
The low intake of fruits and vegetables is a global issue. This research aimed to determine the association of fruit and vegetable intake with waist circumference and barriers of intake. A total of 279 female students from the International Islamic University Malaysia, Kuantan, were recruited through convenience sampling and provided with a set of questionnaires to identify their fruits and vegetable intake. The waist circumference of respondents was measured. The majority of students consumed only one serving of fruit and vegetable per day, which is less than the levels recommended by the Malaysian Dietary Guideline. Only 9.0% of students had a fruits intake of two servings/day, while 6.5% had a vegetable intake of three servings/day which meets the recommendation. There was no significant association of fruits and vegetable intake with waist circumference among female students. Non-availability and not delicious were identified as major barriers to fruit and vegetable consumption respectively. In conclusion, the fruit and vegetable intake among the majority of female university students is inadequate. Thus, there is a need to increase awareness and develop strategies to promote adequate fruit and vegetable intake among this specific target group.